IMPLEMENTASI STRATEGI BERMAIN PERAN DENGAN STIK BONEKA UNTUK MENINGKATKAN KREATIVITAS DAN KEMAMPUAN BERBICARA BAHASA INGGRIS - Yuli Astuti Hasanah (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2019)
The research investigated how the implementation of stick puppet role play in enhancing the speaking ability is. The reseach method used was Classroom Action Research proposed by Kemmis and Mc Taggart. The procedures contained five steps: modeling, drafting, creating, rehearsing, dan performing. In modeling, the teacher gave models of several types of conversations. In drafting, the students made the drafs of the conversations while in creating, the students made stick puppets as characterized in the conversations. Next in rehearsing, the students practiced how to do role play using stick puppets while the teacher gave feedback for the improvement. At last, in performing, the students performed the role play and was recorded by the observer. The result showed that from thirty two students, twenty six students got predicate fair, two students got predicate good, and four students got predicate very good. Therefore, 32 students (100 %) were able to reached the criteria of success as their scores were at least or more than 70. The mean score was 74. The highest scores was 85 dan the lowest score is 70. This strategy is able to give positive impacts to the students in delivering the vocabulary, getting the easiness of showing ideas, improving the speaking skill, enhancing excitement, enthusiasm, confidence, and the efectiveness of the strategy. English teachers are suggested to use this strategy in teaching speaking for other language functions and genres. To the future researcher, it is suggested to do research on the receptive skill such as listening and reading as this study focuses on the productives skill especially speaking skill.